Structure and physicochemical properties of octenyl succinic esters of sugary maize soluble starch and waxy maize starch - Miao, Ming; Li, Rong; Jiang, Bo; Cui, Steve W.; Zhang, Tao; Jin, Zhengyu (Food chemistry, 2014)
•OSA-modified food-grade starch with different DS is synthesised.•Starch type affected physical and chemical stability of emulsions.•Tailor-made OSA-SMSS can be used in the preparation of Pickering emulsions. The structure and physicochemical properties of octenyl succinic anhydride (OSA) starches prepared from sugary maize (SMSS) and waxy maize (WMS) were studied and compared. The degree of substitution (DS) increased linearly with the amount of OSA, while the DS of OSA-SMSS was higher than that of OSA-WMS using equivalent modification conditions. FT-IR analysis indicated that two characteristic peaks, at 1725 and 1570cm−1, were observed for OSA-starch. The weight-average of the molar mass (Mw) and z-root mean square radius of gyration (Rz) of SMSS increased with increased OSA esterification substitutions, whereas Mw was reduced and Rz was nearly constant for WMS. The zeta-potential and emulsifying activity increased with DS for starch modified with OSA. OSA-SMSS (DS of 0.0192) was the best material for stable oil-in-water emulsion preparation. The increase of DS in OSA-starch resulted in a substantial reduction of RDS content with an accompanying increase of SDS and RS. This study revealed the potential application of OSA-SMSS as a particle stabilizer of oil-in-water emulsion, which would allow encapsulate and protect functional food components.